2005
DOI: 10.1111/j.1365-313x.2005.02389.x
|View full text |Cite
|
Sign up to set email alerts
|

Alloplasmic effects on mitochondrial transcriptional activity and RNA turnover result in accumulated transcripts of Arabidopsis orfs in cytoplasmic male‐sterile Brassica napus

Abstract: SummaryMitochondrial transcription was investigated in a cytoplasmic male-sterile (CMS) Brassica napus line with rearranged mitochondrial (mt) DNA mostly inherited from Arabidopsis thaliana. The transcript patterns were compared with the corresponding male-fertile progenitors, B. napus and A. thaliana, and a fertility-restored line. Transcriptional activities, gene stoichiometry and transcript steady-state levels were analysed for all protein and rRNA coding genes and for several orfs present in the A. thalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…Moreover, somatic hybridisation between fertile and alloplasmic male sterile tobacco plants leads to the generation of cytoplasmic hybrids (cybrids) with various flower morphologies intermediate between those of the parents and of plants with recombined mitochondrial genomes [19]. This gradient of cybrid phenotypes suggests that CMS might involve several mitochondrial loci, possibly accounted for by the number of latent ORFs expressed in alloplasmic lines [20,21 ].…”
Section: Cms and Alloplasmymentioning
confidence: 98%
“…Moreover, somatic hybridisation between fertile and alloplasmic male sterile tobacco plants leads to the generation of cytoplasmic hybrids (cybrids) with various flower morphologies intermediate between those of the parents and of plants with recombined mitochondrial genomes [19]. This gradient of cybrid phenotypes suggests that CMS might involve several mitochondrial loci, possibly accounted for by the number of latent ORFs expressed in alloplasmic lines [20,21 ].…”
Section: Cms and Alloplasmymentioning
confidence: 98%
“…At the DNA level, unregulated differences in promoter strength may lead to differential gene expression (Muise and Hauswirth, 1992). By comparing mitochondrial transcriptional rates in Arabidopsis and a cytoplasmic male sterile and a fertile line of Brassica napus species-specific transcription rates for several genes (cox1, nad4L, nad9, ccmB, rps7, and rrn5) were demonstrated, most likely a consequence of different promoter strength (Leino et al, 2005). A study comprising all mitochondrial-encoded genes in Arabidopsis revealed distinct transcription rates of genes encoding components of the same multisubunit complex (Giegé et al, 2000).…”
Section: Multilevel Regulation Of Mitochondrial Gene Expressionmentioning
confidence: 99%
“…Differences in the gene promoter strength were observed between plant mitochondrial genes (Brennicke et al, 1999;Fey and Maréchal-Drouard, 1999) even for genes coding for components of the same complex (Giegé et al, 2000). However, the transcriptional activity appears to have only a small effect on transcript abundance because it is largely counterbalanced by processes at different steps of RNA maturation and degradation (Giegé et al, 2000;Leino et al, 2005;Holec et al, 2008). Therefore, it is thought that modulation of transcription is not essential for regulation of expression of genes encoded in mitochondria and that posttranscriptional processes are more important.…”
Section: Introductionmentioning
confidence: 99%